2005
DOI: 10.1021/ol0513701
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Stereoselectivity Using Lewis Acid in the Cyclization of Allenic Aldehydes Catalyzed by Palladium Complex

Abstract: A highly diastereoselective synthesis of 3 is achieved from the reaction of 1 with hexamethylditin catalyzed by palladium complex in the presence of 20 mol % tris(pentafluorophenyl)borane as a Lewis acid additive for a reversal of diastereoselectivity, whereas 2 is formed in the absence of Lewis acid additive. The method described herein is successful with various substrates 1 in good yields and high levels of diastereoselectivity. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…86 Moderate-to-good yields of trans-products 121 were obtained by using B(C 6 F 5 ) 3 as Lewis acid additive.…”
Section: Scheme 34mentioning
confidence: 99%
“…86 Moderate-to-good yields of trans-products 121 were obtained by using B(C 6 F 5 ) 3 as Lewis acid additive.…”
Section: Scheme 34mentioning
confidence: 99%
“…The stereoselectivity of the palladium-catalyzed cyclization of 1,2-diene-7-als with hexamethylditin was controlled by addition of Lewis acid (Eq. (319)) [1418].…”
Section: Other Carbocyclizationsmentioning
confidence: 99%
“…Initial attempts of a distannation reaction of 7 (R 1 =PhCH 2 CH 2 ) with Bu 3 SnSnBu 3 in the presence of a palladium complex followed by addition to benzaldehyde to give 9 a were unsuccessful under various reaction conditions, presumably owing to a lack of reactivity caused by the steric bulkiness of the tributylstannyl group 5. We subsequently observed that the use of Me 3 SnSnMe 3 in the presence of [(π‐allyl) 2 Pd 2 Cl 2 ], which was previously utilized for the cyclization of allene‐aldehydes,3a could also be employed for this purpose. Upon surveying numerous conditions, the following observations emerged: 1) for the first allylic transfer, the use of 1.3 equivalents of 5 and 6 was optimum to prevent subsequent addition of the same aldehyde; 2) for the distannation reaction, the use of 3 mol % of [(π‐allyl) 2 Pd 2 Cl 2 ] in CH 2 Cl 2 at −40 °C for 4 h was most efficient in terms of reaction yields; 3) the formation of 8 was confirmed by NMR spectroscopy after quenching with pH 7 buffer solution; 4) only Me 3 SnSnMe 3 proved to be effective for the transformation; and 5) the use of CH 2 Cl 2 resulted in optimum chemical yields in comparison to other solvents.…”
Section: Methodsmentioning
confidence: 99%